1984
DOI: 10.2307/1938041
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Predation and the Structure of Desert Rodent Communities

Abstract: Communities of granivorous desert rodents may be influenced by either predation risk or resources. To examine the influence of these factors, I manipulated illumination, using lanterns, and resources, using seeds. Foraging behavior is responsive to changes in predation risk; increased illumination reduces foraging in open areas without cover. Foraging behavior is also affected by resource enrichments. Differences among species in habitat selection are correlated with specific abilities to detect and avoid pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
302
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(310 citation statements)
references
References 48 publications
7
302
0
1
Order By: Relevance
“…These results add evidence for the role of rspb.royalsocietypublishing.org Proc R Soc B 280: 20130762 predation risk in structuring ecological communities, particularly terrestrial vertebrate communities, for which there are very limited experimental tests (e.g. [9,10]). …”
Section: Discussionsupporting
confidence: 52%
“…These results add evidence for the role of rspb.royalsocietypublishing.org Proc R Soc B 280: 20130762 predation risk in structuring ecological communities, particularly terrestrial vertebrate communities, for which there are very limited experimental tests (e.g. [9,10]). …”
Section: Discussionsupporting
confidence: 52%
“…Annuals are short-lived, protein-rich plants, which are thought to be a critical resource for breeding in striped mice (Schradin & Pillay 2006). Spatial distribution of small mammals is often associated with dense cover (Asher et al 2004;Hayes et al 2007), probably because predation risk influences foraging activity (Kotler 1984;Anderson 1986;Brown et al 1988). We found that home ranges with little cover were larger, possibly because striped mice avoided areas without cover for foraging.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, predation risk may affect foraging behavior (Pierce et al, 1992) and in turn may help structure communities of prey when risk differs among habitats (Kotler, 1984). Habitats with homogenous cover (Molina) provide small mammals the opportunity to move short distances among foraging patches (i.e., shrub to shrub movement).…”
Section: Discussionmentioning
confidence: 99%